SERUM AND ESTRUS MUCUS ENZYMES ACTIVITIES AND CHEMISTRY OF NORMAL AND REPEAT BREEDER FRIESIAN CATTLE - KADOOM, A K; EL-HENAWY, M A A (The Indian Journal of Animal Reproduction, 2022)
Estrus mucus (EM) and blood (serum) was collected from 40 apparently normal cattle (Normal breeder, NB = 20; Repeat breeder, RB = 20) at the time of insemination for glucose, minerals, alkaline phosphatase (ALP), lactic dehydrogenase (LDH) and α-amylase concentration. In NB cattle, serum glucose and magnesium were low (p<0.05), whereas, calcium and zinc were high (p<0.05) compared to their respective values in RB cattle. In NB cattle, serum ALP was highly active (p<0.05) compared with RB cattle, while LDH was highly active (p<0.05) in both serum and EM of RB compared with NB cattle. Serum α-amylase was similar (p>0.05) in NB and RB cattle, while RB cattle EM had lower (p<0.05) α-amylase. The pregnancy rate calculated after four maximum inseminations and following categorization into NB or RB cattle was 80% and 60%, respectively. In brief, the variations in serum and estrus mucus enzyme activities and chemistry could be associated with breeding success in Friesian cattle.